Interstitial Photocoagulation of Low Anal Fistula using 810 nm Diode Laser: Prospective Study - Mohammed, Mohammed K. (Iraqi Journal of Laser, 2004)
Many conservative sphincter-preserving procedures had been described to be effective in healing of anal fistula without excision or de roofing. Objective: To verify the outcome of mere photocoagulation of the fistula tract on healing of low anal fistula. Materials and Methods: Using 810nm diode laser, the tracts of low anal fistulae in a cohorts of six male patients (mean age of 32 yr) had been photocoagulated by retrograde application of laser light through an orb tip optical fiber threaded in to the tract. Swabs for culture and sensitivity testing were obtained before and after laser application. Patients were followed up regularly to announce fistula healing. Results: Mean laser exposure time was 6.6 min., mean operative time was 19 min., mean hospital stay was 5.9 hrs and mean fistula closure time was 7.7 days. The negative immediate post laser exposure swabs indicate that laser may have a bacteria killing power. There were no evidences of incontinence or recurrence within the mean follow up period of 9 weeks. The feasibility of using the selected laser and accessory was excellent. The basic laser-tissue interaction was thermal photocoagulation without carbonization. Conclusions and Recommendations: Mere photocoagulation of the fistula tract may heal a low anal fistula. Within the chosen parameters of laser application, there was no evidence of damage to the anal sphincter. It is recommended that larger number of cases to be done to allow for proper statistical analysis. High, complicated, and recurrent cases may be included. A longer follow up period to assess intermediate and long term recurrences is recommended.